Impacts of wildfire smoke aerosols on near-surface ozone photochemistry - J. Shen; R. C. Cohen; R. C. Cohen; G. M. Wolfe; X. Jin (Atmospheric Chemistry and Physics)
Wildfires have been an increasing concern for the environment, yet the ozone (O3) production from wildfires remains poorly characterized. Here, we aim to elucidate the role of aerosols from wildfire smoke in near-surface O3 photochemistry by integrating insights from a 0-D box model (F0AM) to a 3-D chemical transport model (GEOS-Chem). While smoke aerosols typically inhibit O3 production through heterogeneous chemical and radiative pathways, we find that for most fires, the O3 enhancement driven by precursor emissions outweighs these aerosol-driven suppression effects. The relative importance of the two aerosol effects varies, with the heterogeneous chemical effect generally overshadowing the radiative effect in the far field of fires. However, near the sources of extremely large fires, the radiative effect dominates, leading to an overall suppression of O3 production. By assessing the chain termination of hydrogen oxide radicals (HOx) and introducing the “light-limited” regime determination in GEOS-Chem, we find that a significant portion of O3 production occurred within light-limited and heterogeneous chemistry-inhibited regimes during the 2020 wildfire season in California. Building on the discovery that both aerosol and nitrogen oxide (NOx) concentrations modulate aerosol influence, we demonstrate that the ratio of surface PM2.5 to tropospheric NO2 column – a metric retrievable from satellite – can serve as an indicator for identifying aerosol-dominated regimes through observations.